PERANCANGAN FILM ANIMASI 2D CERITA RAKYAT SAMBAS ”PERISTIWA DI TANJUNG DATOK” DENGAN METODE MDLC - Agung Damar Jati; Yuda; Noferianto Sitompul; Narti Prihartini; Naufal Aulia Fiermeiza; Vanie Wijaya; U Heri Mulyanto; Lang Jagat; Sri Wahyuni; Erifa Syahnaz (LPPM Universitas Abdurrab, 2026)
Temajuk Village, located in Paloh District, Sambas Regency, West Kalimantan, boasts a unique natural landscape, culture, and rich history. One important part of this village's cultural heritage is the folktale